Evidence for multiple paternity in the school shark Galeorhinus galeus found in New Zealand waters. Issue 5 (12th August 2014) - Hernández, S.; Duffy, C.; Francis, M. P.; Ritchie, P. A.
<x xml:space="preserve">Abstract</x> This study assessed the levels of relatedness of Galeorhinus galeus of progeny arrays using six microsatellite DNA markers. A parentage analysis from five families (mother and litter) from the North Island of New Zealand suggested the occurrence of genetic polyandry in G. galeus with two of the five litters showing multiple sires involved in the progeny arrays. This finding may be consistent with the reproductive characteristics of G. galeus, in which females can potentially store sperm for long periods of time after the mating season.